Dehydroeburicoic Acid, a Dual Inhibitor against Oxidative Stress in Alcoholic Liver Disease - Shasha Cheng; Yi Kuang; Guodong Li; Jia Wu; Chung-Nga Ko; Wanhe Wang; Dik-Lung Ma; Min Ye; Chung-Hang Leung (MDPI AG, 2022)
Alcoholic liver disease (ALD) is a complicated disease which can lead to hepatocellular carcinoma; however, there is a lack of satisfactory therapeutics. Dehydroeburicoic acid (DEA) (1), a triterpenoid isolated from Antrodia cinnamomea, has been reported to act against ALD, but its mechanisms of action are still not clear. In this study, we report for the first time the use of DEA (1) as a dual inhibitor of the Keap1-Nrf2 protein-protein interaction (PPI) and GSK3β in an in vitro ALD cell model. DEA (1) engages Keap1 to disrupt the Keap1-Nrf2 PPI and inhibits GSK3β to restore Nrf2 activity in a Keap1-independent fashion. DEA (1) promotes Nrf2 nuclear translocation to activate downstream antioxidant genes. Importantly, DEA (1) restores the mitochondrial dysfunction induced by ethanol and generates antioxidant activity in the ALD cell model with minimal toxicity. We anticipate that DEA (1) could be a potential scaffold for the further development of clinical agents for treating ALD.